2001
DOI: 10.1128/iai.69.6.3685-3691.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complement Evasion byBorrelia burgdorferi: Serum-Resistant Strains Promote C3b Inactivation

Abstract: The most characteristic features of the Lyme disease pathogens, the Borrelia burgdorferi sensu lato (s.l.) group, are their ability to invade tissues and to circumvent the immune defenses of the host for extended periods of time, despite elevated levels of borrelia-specific antibodies in serum and other body fluids. Our aim in the present study was to determine whether B. burgdorferi is able to interfere with complement (C) at the level of C3 by accelerating C3b inactivation and thus to inhibit the amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
180
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(193 citation statements)
references
References 34 publications
10
180
0
2
Order By: Relevance
“…The strains HB565 (encapsulated, Hic-positive), PR218 (unencapsulated, Hic-positive), and FP13 (unencapsulated, Hic-negative) were incubated with radiolabeled fH, SCR1-7, or SCR8 -20 (7,20, and 30 ng/reaction, respectively) and centrifuged through 20% sucrose. As shown in Fig.…”
Section: Binding Of Fh and Fh Recombinant Constructs To Pneumococcimentioning
confidence: 99%
“…The strains HB565 (encapsulated, Hic-positive), PR218 (unencapsulated, Hic-positive), and FP13 (unencapsulated, Hic-negative) were incubated with radiolabeled fH, SCR1-7, or SCR8 -20 (7,20, and 30 ng/reaction, respectively) and centrifuged through 20% sucrose. As shown in Fig.…”
Section: Binding Of Fh and Fh Recombinant Constructs To Pneumococcimentioning
confidence: 99%
“…It has been suggested that resistance to complement-mediated killing increases virulence of pathogens and also plays an important role for host specificity [7]. The three human pathogenic genospecies of the B. burgdorferi sensu lato complex, B. burgdorferi, B. garinii, and B. afzelii, differ in their susceptibilities to human complement-mediated lysis [8][9][10][11][12][13]. We have recently reported that serum resistance of Borrelia correlates directly with the acquisition of fluid-phase human complement regulators factor H and FHL-1 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Direct activation of complement via the alternative or the mannose-binding lectin pathway results in opsonization and formation of the lytic membrane attack complex leading to killing of the invading microorganisms (10). An increasing number of microorganisms pathogenic to humans, including B. burgdorferi (11)(12)(13), Neisseria gonorrhoeae (14), Neisseria meningitidis (15), Streptococcus pyogenes (16 -19), and Streptococcus pneumoniae (20), resist complementmediated killing by coating their surfaces with host-derived fluid phase negative complement regulators of the alternative pathway, factor H, and/or factor H-like protein 1 (FHL-1). 1 Factor H and FHL-1 belong to a protein family that is structurally composed of individually folded protein domains, termed short consensus repeats (SCRs), or complement control protein modules (21,22).…”
mentioning
confidence: 99%